Evaluation of a Support Group for Fathers of Children with Autism Spectrum Disorder - Elfert, Miriam; Mirenda, Pat (Canadian Journal of Counselling and Psychotherapy, 2015)
This study evaluated the impact of a support group designed for fathers of children with autism. Two groups of 6 fathers each attended 8 weekly sessions that focused on various topics related to parenting a child with autism. Pre- and post-intervention, participants completed measures of depression, marital adjustment, parenting stress, optimism, coping strategies, and social validity. Participants in one group also completed these measures 4 months later. Results indicated no significant changes on all but one measure; however, participants strongly endorsed the utility of the support group experience. Results are discussed with reference to previous research, limitations, and clinical recommendations.